Coral resilience in marginal reefs of South Sulawesi, Indonesia - FUNTY SEPTIYAWATI POLAPA; CHAIR RANI; JAMALUDDIN JOMPA; SUHARTO SUHARTO (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Polapa FS, Rani C, Jompa J, Suharto. 2026. Coral resilience in marginal reefs of South Sulawesi, Indonesia. Biodiversitas 27 (3): d270333. https://doi.org/10.13057/biodiv/d270333. Coral reefs face escalating global and local threats, yet data on coral resilience to inform rehabilitation strategies remain limited, especially in marginal environments. We compared coral community structure and water quality between marginal and reference reefs in South Sulawesi, Indonesia, to identify stress-adapted genera with restoration potential. Generic diversity was comparable between marginal (16.3±7.5 genera) and reference sites (17.5±3.5 genera), but reference reefs exhibited 2.6× higher coral abundance. Coral abundance showed a strong negative correlation with water quality (r = -0.82). Non-metric multidimensional scaling revealed clear community segregation between reef types, with reef type explaining 37.6% of the variation in composition. Using performance ratios (marginal/reference abundance), we identified Turbinaria (exclusive to marginal sites), Platygyra (ratio = 4.60), Dipsastraea (4.00), and Galaxea (3.13) as genera with exceptional adaptive potential under marginal conditions. Despite a lower performance ratio (0.26), Porites maintained the highest absolute abundance across all sites, highlighting its ecological importance. Our findings provide science-based criteria for coral species selection in restoration programs. We recommend a combined strategy, prioritizing high-performance-ratio genera (Turbinaria, Platygyra, Dipsastraea, Galaxea) for their adaptive advantages while including ecologically dominant, stress-tolerant taxa like Porites to enhance restoration success. This recommendation is specifically targeted for reefs experiencing moderate water quality degradation (STORET scores 12-18) and elevated sedimentation as documented at our nearshore marginal sites in South Sulawesi. This targeted approach leverages marginal reefs as reservoirs of stress-adapted genotypes, offering a practical strategy for enhancing reef recovery in rapidly changing tropical seascapes. Our study underscores the conservation value of marginal reefs and provides actionable insights for reef restoration in Indonesia and similar regions facing cumulative environmental pressures.